Optimasi Adsorpsi Ion Mn2+ Pada Silika-GPTMS Dimodifikasi Dengan Sulfonat - Pratama, Yuda; Oktavia, Budhi; Khair, Miftahul; Sari, Trisna Kumala (Departemen Kimia FMIPA UNP, 2024)
Manganese is one of the heavy metals that can pollute waters. This is caused by the use of pesticides and steel industry waste. Adsorption is one method that can be used to separate manganese metal. The adsorbent that is often used in adsorption is silica gel. However, the effectiveness of silica gel in absorbing heavy metal ions is very low, so modification is needed to increase the absorption capacity of silica gel to heavy metal ions. The purpose of this research is to obtain optimum conditions and sorption capacity of sulfonate-modified Silica-GPTMS in adsorbing Mn2+ ions and its adsorption isotherm. This study used batch method for adsorption process by varying pH and contact time. The results of absorption capacity at the optimum conditions of pH 4 and contact time 30 minutes.